Serum iron level after ingestion of repeated dose of iron shortly after and 2 hours after meal - Sri Kadarsih Soejono, Lukman Hakim, Erna Kristin, Mohammad Hakim, (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2009)
Background: The prevalence of iron deficiency anemia in pregnant women is estimated to be higher than nonpregnant women. Ironsupplementation program has been proven clinicallyto improvethe hemoglobin (Hb)level of pregnant women. The absorption of iron is affected by food, therefore iron has to be given 2 hours after meal. However, in practice, iron was given shortly after meal. The physiologicalchange in pregnant women affects drug absorption, distribution, and eliminationphases. Objective: To understand serum iron level after ingestion of repeated dose of iron shortly after and 2 hours after meal for 12 weeks in trimester 2 pregnant women with iron deficiency anemia. Method: The research design was a phase IIclinical trial. Subjects were 24 trimester 2 pregnant women with iron deficiency anemia, classified into two groups, who were treated as follows: The first group was consisted of 12 women with irondeficiency anemia, treated with twice-a-day ferrous sulphate tablet @300 mg orally,given shortly after meal for 12 weeks; the second group was consisted of 12 women with iron deficiency anemia, treated with twice-a-day ferrous sulphate tablet @300 mg orally, given 2 hours after meal for 12 weeks. Bloodsamples were taken in week 2, 4, 6, 8, 10, and 12 after treatment. Serum (ferric) iron level was measured with Vitros Fe Slides method. Result: Minimum,maximum, and average steady-state ironlevels (Css min, Css max, Css average) of treatment 1 were 104.1 ::I:14.03 ug/dL, 96.44::1:13.22 ug/dL, and 112.38::1:14.03 ug/dL (mean ::I:SEM),respectively; while minimum, maximum, and average steady-state iron levels (Css min, Css max, Css average) of treatment 2 were 125.77::1:9.31 ug/dL, 118.03::1:9.21 ug/dL, and 125.77::1:9.31 ug/dL (mean::l:SEM),respectively. No statistical significant difference was found within treatment in minimumsteady-state level between week 2, 4, 6, 8, 10, 12 after treatment. There was also no significant difference in minimumsteady-state level between treatment groups in week 2, 4, 6, 8, 10, and 12. Conclusion: There were no differences in serum iron level after ingestion of repeated dose of ironshortly after and 2 hours after meal for 12 weeks intrimester 2 pregnant women with iron deficiency anemia.